The comparison of salivary level of estrogen and progesterone in 1 st , 2 nd and 3 rd trimester in pregnant women with and without geographic tongue - Parichehr Ghalayani; Atefeh Tavangar; Firoozeh Nilchian; Navid Khalighinejad (Wolters Kluwer Medknow Publications, 2013)
Background: Geographic tongue (GT) was first reported as a wandering rash of the tongue in 1831; however, its etiopathogenesis remains unclear. Increased prevalence of GT has been documented in the pregnancy. The aim of this study was to compare the level of salivary estrogen and progesterone in pregnant women with and without GT. Materials and Methods: This analytical-descriptive study consisted of 26 pregnant women (13 with GT, 13 without GT) with an age range between 18 years and 45 years. The estrogen and progesterone level was measured during 1 st , 2 nd and 3 rd trimester of pregnancy. Saliva sampling was performed to determine the level of sex hormones. The samples were stored at -80°C and determined by Eliza method. The results were analyzed by t-test and repeated measure ANOVA (α = 0.05). Results: The mean level of estrogen for control and case group was 49.4and 52.33 in the 1 st , 71.05 and 74.12 in the 2 nd and 109.1 and 112.16 in the 3 rd trimester respectively. The mean level of progesterone was 0.72 and 0.72 in the 1 st , 1.14 and 1.21 in the 2 nd and 1.3 and 1.28 in the 3 rd trimester of pregnancy for the control and case groups respectively. Even though, there was no significant difference regarding the level of sex hormones between case and control groups (P > 0.05), but the difference between the level of these hormones during 3 trimesters of pregnancy was significant in each group (P = 0.001). Conclusion: The level of sex hormones is not the only etiologic factor of GT in pregnant women, but other factors such as genetic potential, human leukocyte antigen marker and stress may aggravate the incidence of this lesion.